Clinical Outcomes and Postoperative Radiographic Assessment of Osteoplastic Hemilaminectomy in the Treatment of Lumbar Foraminal Nerve Root Compression - Nojiri, Hidetoshi; Oha, Fumihiro; Hasegawa, Yuichi; Hashimoto, Tomoyuki; Ishijima, Muneaki; Tanaka, Masaru; Hara, Hiroyuki; Shimamura, Yukitoshi; Kanayama, Masahiro; Endo, Tsutomu; Tsujimoto, Takeru (Spine Surgery and Related Research, 2021)
Introduction: Osteoplastic hemilaminectomy for the treatment of lumbar foraminal nerve root compression is a safe technique as the exiting nerve root can be directly observed during neuroforaminal decompression without spinal fusion. Moreover, this procedure allows anatomical reconstruction of the posterior elements. However, there might be a potential risk for the progression of lumbar segmental instability after performing this procedure. This study aimed to review the radiographic and clinical outcomes of osteoplastic hemilaminectomy for the treatment of lumbar foraminal nerve root compression.Methods: We retrospectively reviewed 51 patients who underwent osteoplastic hemilaminectomy with a minimum follow-up of 2 years. The clinical outcomes were evaluated using the visual analog scale (VAS) for low back pain, leg pain, and numbness and the Japanese Orthopaedic Association (JOA) score. Lumbar segmental instability was evaluated as a radiographic assessment using functional radiography. The mean follow-up period was 65 months.Results: The preoperative VASs for low back pain, leg pain, and numbness were 46±31, 72±26, and 43±34, respectively, which were improved to 24±23, 19±23, and 19±23, respectively. The JOA score was also improved from 14±5 to 22±4. Three patients (5.9%) were reoperated due to recurrent disc herniation within 2 years following surgery. In addition, three patients (5.9%) developed postoperative lumbar segmental instability but did not require additional surgery.Conclusions: The current study revealed that 94.1% of the patients who underwent osteoplastic hemilaminectomy achieved a significant improvement in the clinical outcomes and did not require additional surgery within 2 years following the procedure. Over a 5-year follow-up on average, 5.9% of the subjects developed postoperative lumbar segmental instability; however, they have maintained acceptable clinical conditions.